Determinan Terhadap Penghindaran Pajak (Tax Avoidance) - Inggriyani, Inggriyani (Universitas Muhammadiyah Metro, 2023)
This research was conducted to examine the effect of Return On Assets, Leverage, Firm Size, Fiscal Loss Compensation, Institutional ownership, corporate risk, growth, and Independent Board of Commissioners have an effect on Tax Avoidance. The population of this research is population is all mining companies listed on the Indonesia Stock Exchange from 2016-2020. The sample selection used a purposive sampling technique and obtained 71 samples. Data analysis using multiple linear regression analysis with IBM SPSS version 25 program. The results showed that fiscal loss compensation and institutional ownership have a negative influence on tax avoidance, while ROA, leverage, firm size, growth, and Independent Board of Commissioners have an influence on tax avoidance.